The Effectiveness of the Work of Government Employees with Employment Agreement (AGEEA) in an Increase Public Service on the Secretariat District of South Manokwari, West Papua Province - Welfris Diego Armando (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2018)
Acceptance Government Employees with Employment Agreement (AGEEA) or labor of honorary in the scope of local government in South of Manokwari, is because of lack of Apparatus Civil State (ACS), but admissions process is not through phases test competency or through Analysis of the Needs of Employees so the labor of honorary who received has a very low ability, but because so many labors of honorary, district government in  South of  Manokwari must spend a very large cost to finance the labor of honorary. However, in terms of public service, still considered need to be improved. Therefore the author interested to investigate the research entitled "The Effectiveness of the Work of Government Employees with Employment Agreement (AGEEA) in an Increase Public Service on the Secretariat District of South Manokwari, West Papua Province".This study aims to know how the effectiveness of the workforce honorary in an increase public service on the Secretariat District in South of Manokwari, supporting factors and inhibitor labor of honorary in doing increase public services as well as a strategy to overcome of factors inhibitor of the effectiveness of the workforce honorary in an increase public services performed labor of  honorary on the Secretariat District in South of Manokwari. The method used is qualitative research methods. Data collection techniques used is the interview, observation, and documentation. Based on the research conducted, it needs to be the addition of an Apparatus Civil State (ACS), the application of regulation Regent maximum, activities to improve the cooperation, give a reward and punishment. Job description according to education and traffic need for an increase in human resources. Development office building and facilities that support staff in the work and provide the increase of human resources through human capital investment for the labor of honorary eligible.